The Role of Partnership in Value Chain of Sweet Potato in Regency of West Java (Case Study of PT Galih Estetika Indonesia Partnership) - Eva Farichatul Aeni; Amzul Rifin; Netti Tinaprilla (School of Business, IPB University (SB-IPB), 2017)
The partnership between the farmers and PT Galih Estetika Indonesia as the exporter company in the field of sweet potato processing is expected to support the development of sweet potato agribusiness in Kuningan Regency and become one of the solutions for farmers’ problems. Termination of partnership contracts undertaken by the farmers will have an impact on the implementation of partnerships, company operations as well as the value chain. This study aims to analyze the pattern of partnership, degree of partnership, value chain structure, value chain governance, farmers’ income (partner and non-partner) and margin. The method of data processing and data analysis used the descriptive analysis qualitative and quantitative descriptive analysis. The results showed that the pattern of partnership that is formed is a centralized pattern with the degree value of partnership of 716 (madya pattern). The structure of the value chain by mapping the actors and their activities result in relationships and coordination between the parties. Farmers with companies belong to the modular type in VCG. Economic benefits indicate that net income of partner farmers is Rp22,157,828/Ha, while non-partner farmers obtain Rp12,306,789/Ha and the smallest margin is obtained by the coordinator. The analysis shows that farmers' incomes are larger, but partnership planning has not been ideal. Therefore, the roles of farmers, companies and related agencies are required in the running of the ideal sweet potato partnership program.Keywords: sweet potato partnership, partnership pattern, value chain, value chain governance, revenue